2017
DOI: 10.1097/md.0000000000007310
|View full text |Cite
|
Sign up to set email alerts
|

Computer-designed surgical guide template compared with free-hand operation for mesiodens extraction in premaxilla using “trapdoor” method

Abstract: The aim of this study was to introduce a novel method of mesiodens extraction using a vascularized pedicled bone flap by piezosurgery and to compare the differences between a computer-aided design surgical guide template and free-hand operation.A total of 8 patients with mesiodens, 4 with a surgical guide (group I), and 4 without it (group II) were included in the study. The surgical design was to construct a trapdoor pedicle on the superior mucoperiosteal attachment with application of piezosurgery. The bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
2
17
1
Order By: Relevance
“…This may be because the guide technique helped the surgeons understand the precise 3D localization of STs, and provided direct access which increased the surgeons' confidence in performing the surgery and positively affected the operation time. A previous clinical study of eight patients with impacted STs revealed that the average operation time of the surgical guide technique for impacted ST extraction was approximately 16 min, which was approximately 4 min shorter than that of the conventional technique [17]. In the present study, the surgical guide technique needed approximately 2 min, whereas the conventional technique needed approximately 3.5 min.…”
Section: Discussioncontrasting
confidence: 40%
“…This may be because the guide technique helped the surgeons understand the precise 3D localization of STs, and provided direct access which increased the surgeons' confidence in performing the surgery and positively affected the operation time. A previous clinical study of eight patients with impacted STs revealed that the average operation time of the surgical guide technique for impacted ST extraction was approximately 16 min, which was approximately 4 min shorter than that of the conventional technique [17]. In the present study, the surgical guide technique needed approximately 2 min, whereas the conventional technique needed approximately 3.5 min.…”
Section: Discussioncontrasting
confidence: 40%
“…This could be attributed to the greater confidence of the participants using the guide. This finding was consistent with those of previous studies demonstrating that the use of a guide decreased the duration of dental surgery [ 17 , 18 ]. This time reduction for teeth preparation is clinically significant.…”
Section: Discussionsupporting
confidence: 93%
“…Improvements to the technique may derive by the use of computer-designed customized cutting guides, which allow for a pre-planned accurate outline of the osteotomies and, subsequently, better lid realignment and stability [47]. This approach may further improve the outcomes of the bone lid technique [12,27,38,47,61], making it more easily applicable as well. This topic should be further investigated with future RCTs comparing free-hand vs computer-guided bone lid surgery.…”
Section: Discussionmentioning
confidence: 99%